Evaluasi persepsi praktisi olahraga terhadap penerapan prinsip transparansi dan keadilan dalam kebijakan olahraga nasional - Amali, Zainudin; Castyana, Billy; Mega Anggita, Gustiana; Arif Ali, Mohammad; Rahayu, Tandiyo (Universitas Nusantara PGRI Kediri, 2021)
National sports policies exist to regulate the sports system so that all can feel the benefits and no one feels disadvantaged. However, it is not yet known whether the existing policies are transparent and fair, so this quantitative descriptive study was conducted to determine the extent of the perception of sports practitioners regarding the application of the principles of transparency and fairness to national sports policies. With the survey method, 455 sports practitioners were selected through purposive sampling to provide answers through a questionnaire on the google form. The statement comes from the variables of transparency and fairness with asymmetric Likert as the answer choice, which is strongly agree to strongly disagree. The results show that 28.48% of sports practitioners strongly agree and 59.81% choose to agree that the principle of transparency has been applied to sports policy, although there are 11.02% of sports practitioners who disagree and 0.69% strongly disagree. On the other hand, 35.22% of sports practitioners strongly agree and 59.84% agree that the principle of fairness has been applied in the implementation of national sports policies. However, there are 4.84% of sports practitioners who disagree and 0.11% strongly disagree if the principle of fairness has been applied. It can be concluded that the principles of transparency and fairness in national sports policies have been felt by sports practitioners, one of which is through the ease of obtaining information related to sports policies to the distribution of awards and coaching.